2011
DOI: 10.2147/rrtm.s20571
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationships between dengue fever knowledge and Aedes aegypti breeding in St Catherine Parish, Jamaica: a pilot of enhanced low-cost surveillance

Abstract: Dengue fever has re-emerged as an increasingly significant global health threat amid diminishing resources pledged for its control in developing nations. Efforts to limit breeding of the dengue vector Aedes aegypti are often hampered by lack of community awareness of the disease. Methods: Sixty-eight households in St Catherine Parish, Jamaica completed a pilot knowledge, attitude, and practice questionnaire as part of a routine container survey for presence of A. aegypti larvae. Results: Infestation levels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…The use of preventive measures was widespread in the community with four of five households reporting at least one method to avoid contact with mosquitos. Repellents and insecticide sprays were the most popular among the different anti-mosquito methods reported, in agreement with a study in Jamaica 26 and Puerto Rico. 27 Contrary to our results, studies in Sri Lanka, 28 Pakistan, 29 and Laos 30 found that mosquito nets were a popular method of protection against dengue.…”
Section: Discussionsupporting
confidence: 89%
“…The use of preventive measures was widespread in the community with four of five households reporting at least one method to avoid contact with mosquitos. Repellents and insecticide sprays were the most popular among the different anti-mosquito methods reported, in agreement with a study in Jamaica 26 and Puerto Rico. 27 Contrary to our results, studies in Sri Lanka, 28 Pakistan, 29 and Laos 30 found that mosquito nets were a popular method of protection against dengue.…”
Section: Discussionsupporting
confidence: 89%
“…The ‘overall knowledge score’ (maximum score: 17 points) was derived by adding one point per correct answer, which equalled the sum of the transmission (maximum score: 1) and the symptom (maximum score: 16) knowledge scores ( S1 Table ). This methodology and scoring of knowledge was used in several other studies [ 31 – 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…This might be due to apprehension towards unfamiliar symptoms of dengue fever prompting the individual to seek immediate treatment. 21,22,24,25,[26][27][28] Our study found that there were no association found between knowledge and attitude of dengue and sociodemographic characteristics of the respondents. In term of age, other studies found that the older age has higher knowledge score compared to younger age.…”
Section: Discussionmentioning
confidence: 54%